2010
DOI: 10.1007/s00198-010-1183-8
|View full text |Cite
|
Sign up to set email alerts
|

Laser 904 nm action on bone repair in rats with osteoporosis

Abstract: Low-level 904-nm laser (50 mJ/cm(2)) accelerated the repair process of osteopenic fractures, especially in the initial phase of bone regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 25 publications
2
22
0
3
Order By: Relevance
“…LLLT also has various effects in bone tissue according to the application parameters, such as the type of laser used, energy density (J/cm 2 ), time and frequency of irradiation, and wavelength, which can contribute effectively to the stimulation of bone cells by increasing the osteoblastic activity at the defect area. 2,14,22 Thus, the biomodulatory effects of laser irradiation seem to be dose dependent. 2 In addition, the method of application can also influence the biostimulatory effect of the laser on bone cells.…”
Section: 18mentioning
confidence: 99%
See 2 more Smart Citations
“…LLLT also has various effects in bone tissue according to the application parameters, such as the type of laser used, energy density (J/cm 2 ), time and frequency of irradiation, and wavelength, which can contribute effectively to the stimulation of bone cells by increasing the osteoblastic activity at the defect area. 2,14,22 Thus, the biomodulatory effects of laser irradiation seem to be dose dependent. 2 In addition, the method of application can also influence the biostimulatory effect of the laser on bone cells.…”
Section: 18mentioning
confidence: 99%
“…31 Moreover, some authors have demonstrated positive biostimulatory effects of LLLT with longer wavelengths (904-980 nm) on the bone regeneration process. 14,24,32 In this study, a Ga-Al-As diode laser operating at a wavelength of 940 nm was used due to its improved tissue penetration profile. We thought that the low-intensity irradiation from a 940 nm GaAlAs diode laser used in this study would be able to promote bone healing at a deeper level in healthy rats.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pires-Oliveira et al 2010 [16] demonstrated the action of As-GA laser irradiation (904 nm, 50 mJ/cm 2 ) on bone repair in tibia of osteopenic rats using bone densitometry and histomorphometric analyses. The authors found this irradiation model accelerated the repair process in osteopenic fractures, especially in the initial phase of bone regeneration.…”
Section: Open Accessmentioning
confidence: 99%
“…This process results in beneficial therapeutic outcomes including but not limited to the alleviation of pain or inflammation, immunomodulation, and promotion of wound healing and tissue regeneration.^ [1]. PBM therapy was found to have multiple clinical benefits, which includes reducing pain [2][3][4][5][6][7], improving wound healing [8][9][10][11], accelerating bone healing [12][13][14][15][16][17], promoting osteointegration [18], facilitating orthodontic tooth movement [19][20][21][22][23][24][25][26], stimulating bone formation [27][28][29][30][31], and improving periodontal tissue repair and decreasing inflammation and root resorption [23,26,32]. The light sources were laser or a light-emitting diode (LED).…”
Section: Introductionmentioning
confidence: 99%